(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This research examines the role of the technological revolution in shaping the economy of the Republic of Uzbekistan over the past nine years. Particular attention is given to the “Digital Uzbekistan–2030” strategy and its role in expanding e-government services, digital payment systems, and information and communication technologies. The study shows that the introduction of modern technologies has contributed to improving productivity, increasing transparency in public services, and creating new business opportunities. At the same time, certain challenges remain, including the need for qualified specialists, development of digital infrastructure, and reduction of the digital gap between regions.